The Relevance Of Economic Policy In Khulafal Rasyidin And Modern Era - Kurniadi, Kurniadi; Mu'min, Muh. Dian Nur Alim; Amir, AM Nur Atma; Misbahuddin, Misbahuddin; Siradjuddin, Siradjuddin (Universitas Muhammadiyah Makassar, 2023)
After the death of Rasulullah saw, the country's economic system, especially in economic matters, was taken over by the khulafaul Rashidun. There were four leading figures in this phase, namely Abu Bakar Assiddiq, Umar bin Khattab, Uthman bin Affan, and Ali bin Abi Talib. The caliphs carried out their government system based on the guidance of the Prophet Muhammad based on the Qur'an and Sunnah. The purpose of this study was to find out the policies among the caliphs in managing the country's economic problems, as well as the relevance of the economic system during the Khulafaul Rashidun era to modern times. This research is a